EVALUATION OF ACUTE AND CHRONIC TOXICITY, COGNITION IN ADULT ZEBRAFISH WITH VASICINE; A PROSPECTIVE COGNITION ENHANCER IN NEUROLOGICAL DISORDERS - ARTHI BALSUNDARAM; DARLING CHELLATHAI (International Journal of Pharma and Bio Sciences, 2016)
Traditionally the herb Justicia adhatoda has been used widely as antitussives, antispasmodic, and abortifacient. But quantitative neurotoxicity studies of Vasicine are scarcely explored. Therefore establishing a toxicity dosage would enable safe therapeutic prescription. There are number of studies which have performed toxicity with adhatoda extract, however isolated Vasicine toxicity profile screening in zebrafish has scarcely been discussed. A whole animal toxicity screen, including cognition, organ pathology and anatomy in orally administered fish would allow screening all vital organs, and behavior as an efficient toxicity study set up. Moreover orally administered vasicine would be subjected to the gastric environment and secondary metabolism allowing a more close comparison to oral route of dosage. Adult zebrafish were treated with different concentrations of vasicine orally and were periodically accessed for a 14 day acute period and 30 day chronic period. Both organ pathology and cognitive studies showed no toxicity on oral administration of a total 18.5 ngfor 30 days. It can be said that vasicine is safe at nanogram quantity for a zebrafish when administered orally. This could translate into milligrams quantity in mammals or micrograms in larger mammals. Hepatic metabolism could render the molecule safer and more efficient. By therapeutic index standards the dosages falls within a wide range of therapeutic potential before inducing toxicity. Since Vasicine with our preliminary docking studies have proven hypothetically to be a prospective molecule in inhibiting cAMP specific phosphodiesterase enzyme (PDE7B) , therapeutic dosages of Vasicine could be promising as a potential therapy in cognitive enhancement for neurological disorders such as Alzheimer’s and Parkinson disease, multiple sclerosis, etc.